Supersmooth Ta2O5/Ag/Polyetherimide Film as the Rear Transparent Electrode for High Performance Semitransparent Perovskite Solar Cells. Issue 4 (12th December 2018) - Ying, Zhiqin; Chen, Wei; Lin, Yi; He, Zhenfei; Chen, Tian; Zhu, Yudong; Zhang, Xusheng; Yang, Xi; Djurišić, Aleksandra B.; He, Zhubing
Abstract: Although it exhibits great potential as the rear transparent electrode (RTE) material in semitransparent devices, the ultrathin silver film still faces some significant challenges, such as surface plasmonic effect induced optical loss, the conflict between conductivity and transmittance, and the band level mismatch at device interfaces. In this work, a novel combination of ZrAcac/PEI/Ag/Ta2 O5 is employed as the RTE of the semitransparent perovskite solar cells in the planar inverted device structure of "indium‐tin‐oxide (ITO)/NiO x /MAPbI3 /PC61 BM/ZrAcac/PEI/Ag/Ta2 O5 ." Interface engineering with ZrAcac/PEI enables a significant increase in the device efficiency for 100 nm thick Ag electrode, from 17.48% to 18.84%. Ultrathin 9 nm Ag film coated on polyetherimide (PEI) exhibits a root‐mean‐square roughness of 0.7 nm and a sheet resistance of 8.7 Ω □ −1, which results in the typical device conversion efficiency of 13.40% and an average transmittance (AT) of 43.75% in wavelength region from 500 to 1200 nm simultaneously. That remarkable enhancement in AT from 12.47% to 43.75% can be ascribed to the synergy effect of Ta2 O5 and the ultrathin silver film in optics. The successful interface engineering of RTE paves an alternative and promising way for high performance semitransparent solar cells, and definitely broadens the scope of their applications. Abstract : A novel combination of polyetherimide/Ag/Ta2 O5 is employed as the rear transparent electrode of the semitransparent perovskite solar cells, resulting in a typical device conversion efficiency of 13.40% and an average transmittance of 43.75% by the synergy effect of Ta2 O5 and Ag.